Governance of Dagho fishing port, Sangihe Islands Regency, Indonesia - Dalengkade, Yulianus D; Wantasen, Adnan S; Reppie, Emil; Luasunaung, Alfret (AQUATIC SCIENCE & MANAGEMENT, 2013)
Sangihe Islands Regency has a coastal fishing port located in the village of Dagho sub-district of Tamako. As the only the coastal fishery port in the regency it is expected to provide support in the development of regional economy. This research intended to study the status of management sustainability in Dagho coastal fishing port and analyze policy directions in sustainability management of the coastal fishing port Dagho. Research results showed that the status of sustainability management of the coastal fishing port Dagho belongs to the category of less sustainable fisheries. Towards a policy of management of coastal fishing port Dagho port management is attainment of sustainability according to economic and institutional functions.Â Kabupaten Kepulauan Sangihe memiliki Pelabuhan Perikanan Pantai (PPP) yang terletak di Kampung Dagho, Kecamatan Tamako. Sebagai satu-satunya PPP yang ada di kabupaten tersebut diharapkan akan memberikan dukungan dalam pengembangan perekonomian daerah. Penelitian ini bertujuan untuk mengkaji status keberlanjutan dalam pengelolaan PPP dan menganalisis arah kebijakan multipihak dalam keberlanjutan penatakelolaan PPP Dagho. Hasil penelitian menunjukkan status keberlanjutan pengelolaan pelabuhan perikanan tersebut masuk dalam kategori kawasan pelabuhan perikanan â€œkurang berkelanjutanâ€. Sedangkan arah kebijakan pengelolaan PPP Dagho adalah terwujudnya pengelolaan pelabuhan yang berkelanjutan menurut skenario fungsi ekonomi dan kelembagaan.